2009
DOI: 10.2478/v10047-009-0024-z
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of the Combustion Dynamics of Renewable & Fossil Fuel Co-Fire in Swirling Flame

Abstract: The complex experimental research into the combustion dynamics of renewable (wood biomass) and fossil (propane) fuel co-fire in a swirling flame flow has been carried out with the aim to achieve clean and effective heat production with reduced carbon emissions. The effect of propane co-fire on the formation of the swirling flame velocity, temperature and composition fields as well as on the combustion efficiency and heat output has been analysed. The results of experimental study show that the propane supply i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2017
2017

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 3 publications
0
5
0
Order By: Relevance
“…For magnetic flux density, two magnetization directions, perpendicular to the flow direction and aligned with the flow direction, were considered (see Figs. 7,8). The flux density in Figs.…”
Section: Mathematical Modelling and Numerical Resultsmentioning
confidence: 97%
“…For magnetic flux density, two magnetization directions, perpendicular to the flow direction and aligned with the flow direction, were considered (see Figs. 7,8). The flux density in Figs.…”
Section: Mathematical Modelling and Numerical Resultsmentioning
confidence: 97%
“…The swirl effect on the flame temperature, composition of products and combustion efficiency was measured and analyzed using a Testo-350XL gas analyzer. The results of a previous experimental study into the formation of the swirling flame dynamics [11] allows suggesting that -for the given configuration of experimental setup -the secondary swirling air promotes formation of upstream and downstream swirling air flows with the swirl flow reversing from the biomass layer. To confirm the upstream swirl flow formation below the tangential nozzles, experiments were run on the influence exerted by cold air swirl effect on the propane flame.…”
Section: Methodsmentioning
confidence: 92%
“…To carry out the experimental study of the swirl effects on the formation of flow dynamics at thermo-chemical conversion of the batch-size biomass samples, the cylindrical channel combines a biomass gasifier and a combustor, downstream of which the combustion of volatiles is developing [11]. The gasifier is charged with biomass pellets of the total mass of 240g.…”
Section: Methodsmentioning
confidence: 99%
“…From previous researches Zake et al 2009) it was concluded that gas and wood fuel co-firing promotes the enhanced wood fuel gasification at the primary stage of the swirling flame formation, while the additional heat injection into the flame reaction zone results with an enhanced burnout of the volatiles. There is CHP plant in Denmark, where wood chips are co-fired with natural gas.…”
Section: Introductionmentioning
confidence: 98%